$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

# 4.9: Hyperbolic Functions

[ "article:topic", "hyperbolic functions", "authorname:green" ]

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$

### Definition of the Hyperbolic Functions

We define the hyperbolic functions as follows:

$\sinh x = \dfrac{e^x - e^{-x}}{2},$

$\cosh x = \dfrac{e^x + e^{-x}}{2},$

$\tanh x = \dfrac{\sinh x}{\cosh x}.$

Properties of Hyperbolic Functions

1. $$\cosh^2 x - \sinh^2 x = 1$$,
2. $$\dfrac{d}{dx} \sinh x = \cosh x$$,
3. $$\dfrac{d}{dx} \cosh x = \sinh x$$.

Proof of Property A

We find

\begin{align*} \cosh^2 x - \sinh^2 x &= \left( \dfrac{e^x+e^{-x}}{2} \right)^2 - \left( \dfrac{e^x-e^{-x}}{2} \right)^2 \\[5pt] &= \dfrac{e^{2x}+2+e^{-2x}}{4} - \dfrac{e^{2x}-2+e^{-2x}}{4} \\[5pt] &= \dfrac{4}{4} =1. \end{align*}

$$\square$$

### The Derivative of the Inverse Hyperbolic Trig Functions

$\dfrac{d}{dx} \sinh^{-1} x = \dfrac{1}{\sqrt{1+x^2}},$

$\dfrac{d}{dx} \cosh^{-1} x = \dfrac{1}{\sqrt{x^2-1}},$

$\dfrac{d}{dx} \tanh^{-1} x = \dfrac{d}{dx} \coth^{-1} x = \dfrac{1}{1-x^2},$

$\dfrac{d}{dx} \text{sech}^{-1} x = \dfrac{1}{x\sqrt{1-x^2}},$

$\dfrac{d}{dx} \text{csch}^{-1} x = \dfrac{1}{x\sqrt{1+x^2}}.$

Proof of the third identity

We have

$\tanh (\tanh^{-1} x) = x. \nonumber$

Taking derivatives implicitly, we have

$\dfrac{d}{dx} \text{sech}^2 (\tanh^{-1} x = \tanh^{-1} x = 1. \nonumber$

Dividing gives

$\dfrac{d}{dx} \tanh^{-1} x = \dfrac{1}{\text{sech}^2 (\tan^{-1} x)}. \nonumber$

Since

$\cosh^2(x) - \sinh^2(x) = 1, \nonumber$

dividing by $$\cosh^2(x)$$, we get

$1 - \tanh^2(x) = \text{sech}^2(x) \nonumber$

so that

\begin{align*} \dfrac{d}{dx} \tan^{-1} x &= \dfrac{1}{1-\tanh^2 (\tanh^{-1} x)} \\[5pt] &= \dfrac{1}{1-x^2}. \end{align*} $$\square$$ For the derivative of the $$\text{sech}^{-1} (x)$$ click here. ### Integration and Hyperbolic Functions Now we are ready to use the arc hyperbolic functions for integration. Example $$\PageIndex{1}$$ Evaluate \[ \int \dfrac{dx}{4-x^2} \nonumber

Solution

$\int \dfrac{dx}{4-x^2} = \int \dfrac{1}{4} \int \dfrac{dx}{1-(2/3)^2}\nonumber$

let $$u = \dfrac{x}{2}$$, then $$du = \dfrac{1}{2}dx$$

$\dfrac{1}{2} \int \dfrac{du}{1-u^2}= \dfrac{1}{2}\tanh^{-1} u +C = \dfrac{1}{2} \tanh^{-1} \left(\dfrac{x}{2}\right) + C.\nonumber$

Example $$\PageIndex{2}$$

Evaluate

$\int \dfrac{x}{1-x^4} dx. \nonumber$

Solution

Although this is not directly a derivative of a hyperbolic trig function, we can use the substitution $$u = x^2$$ and $$du = 2x\, dx$$.

To change the integral to

\begin{align*} \dfrac{1}{2} \int \dfrac{du}{1-u^2} &= \dfrac{1}{2} \tanh^{-1} u + C \\[5pt] &= \dfrac{1}{2} \tanh^{-1} (x^2) + C. \end{align*}